Ісламські банки: особливості функціонування та розвитку - Сембер, С.В.; Стойка, В.С.; Легеза, Н.Е. (Економіка промисловості, 2016)
В статті розглянуто особливості становлення, розвитку та функціонування ісламських банків. Авторами досліджено географію поширення та визначено країни, які являються лідерами ісламського банкінгу в сучасній світовій фінансовій системі. Проаналізовано особливості функціонування ісламських банків та вказано на їх відмінність від традиційних. Акцентовано увагу на соціальній відповідальності ісламських банків, яка є їх характерною рисою. В статье рассмотрены особенности становления, развития и функционирования исламских банков. Авторами исследована география расширения и определены страны, которые являются лидерами исламского банкинга в современной мировой финансовой системе. Проанализированы особенности функционирования исламских банков и указано их отличие от традиционных. Акцентировано внимание на социальной ответственности исламских банков, которая является их характерной чертой. The specifics of the development and functioning of the Islamic banks have been examined in the article. The authors have researched the expansion geography and have defined the countries that are the leaders of the Islamic banking in the modern world financial system. The specifics of the Islamic banks development not only in the Middle East but also in the countries of the Asia Pacific region, Europe and the USA have been examined. There has been emphasized on the necessity of formation and specifics of functioning of the Islamic Development Bank as well as on the other organizations that deal with the standards of development of the Islamic banking in accordance with the Sharia demands. The development stages of the Islamic banks in the world financial system have been highlighted: genesis (VIII-XIII centuries), recovery attempt (the 60-s of the XX century), formation (the 70-s of the XX century), development (the 80-90-s of the XX century), business expansion and entrance to the financial markets of the non-Islamic countries (since 2000). The countries that are the leaders of the Islamic banking in the modern world have been defined: Iran, Saudi Arabia, the United Arab Emirates, Bahrain, Malaysia and Great Britain. The specifics of the functioning of the Islamic banks have been analyzed and their difference from traditional ones has been identified. Special attention has been paid to the main values of the Islamic banking and the basic interdictions in accordance with the Sharia laws. The main types of the Islamic banks operations have been examined. The authors have greatly emphasized on the social responsibility of the Islamic banks which is their characteristic feature. The special aspects of functioning of the Islamic banks that are known for their social activity have been analyzed, among which are Jordan Islamic Bank, Islami Bank Bangladesh, Social Investment Bank and Bank Muamalat Malaysia.